Effort at Work and Worker Well-Being in the US - J. Ignacio Gimenez-Nadal; José Alberto Molina; Almudena Sevilla (Institute of Labor Economics (IZA), 2022)
This paper analyses detailed 24-hour diary data from the United States to provide evidence on the relationship between workers' effort and well-being while at work. In doing so, we first measure workers' effort in terms of its timing, its nature, and its composition. Second, we link these three measures of worker effort with data on instantaneous well-being while at work. We find that the lower the number of on-the-job leisure episodes, and the more time workers spend working until on-the-job-leisure, the higher the levels of stress during their work tasks. A back-of-the-envelope calculation based on time use data over the last 4 decades indicates that an increase in the length of time uninterrupted by leisure, observed in the US, is related to increases in worker stress. In analyzing workers' effort and stress during market work activities we contribute to the underdeveloped literature on the determinants of worker happiness while at work, positing the structure of work as an affective factor.
Keywords: D60; J22; J24; 330; time-use; effort at work; stress